Efecto de dos fuentes de materia orgánica como complemento a la fertilización química del cultivo de arroz (oryza sativa), variedad f- 21 en la zona de Babahoyo provincia de Los Ríos - Córdova Oñate, Marcelo José (2011)
The rice (Oryza sativa L.) is consumed by 75% of the world-wide population. In Ecuador, the majors seeded areas are in the provinces of Guayas and the Ríos. Great surface of the plantations is affected by problems of fertility and lost in the yield, due to the evil handling of fertilizers and new sources of mineral matters or biological. The objective of this investigation was to evaluate the effectiveness of the application of several sources of organic matter in mixture with commercial chemical fertilizers, to evaluate its effect on the grain yield and behavior of the culture. The work was realized in the fields, located in the Technical University of Babahoyo, Farming Faculty of Sciences in the Province of Los Ríos, between the months of February and June of the 2010. Nine treatments and four repetitions were investigated. Rice seedtime was realized variety INIAP 15 in 24 parcels of 20 m². The treatments were distributed at random in a design of complete blocks. For the evaluation of averages the test of Tukey to 5% of probabilities was used..........